Tectono‐stratigraphic evolution of the rift and post‐rift systems in the Northern Campos Basin, offshore Brazil. (12th May 2022) - Strugale, Michael; Cartwright, Joe
Abstract: The Campos and Santos Basins have been a focus of subsurface studies since the discovery in 2006 of large accumulations of hydrocarbons in the Early Cretaceous rift and post‐rift strata below Aptian evaporites. In this study, regional 2D seismic lines, a 3D seismic survey and well data were interpreted to reconstruct the tectono‐stratigraphic evolution of the rift and post‐rift stages in the northern sector of the Campos Basin. Detailed 3D seismic interpretation and geological modelling were used to subdivide the pre‐salt sedimentary record. This revealed a diachronous strain distribution along the Guriri Fault System (GFS), a roughly NE‐SW striking fault‐bounded horst that was a focus of rift‐related deformation. The syn‐rift succession is interpreted to be the product of two episodes of rifting (RP1 and RP2) with contrasting fault activity patterns and lithostratigraphy. Volcaniclastics and coarse siliciclastics of RP1 were deposited under WNW‐ESE transtension that formed discontinuous half‐grabens followed by extensive erosion and tectonic inversion. Structurally controlled bioclastic rudstones and hybrid deposits characterize RP2 and were deposited in elongated half‐grabens that delimit the GFS horst, which developed under an NW‐SE extension. Deposition under increasingly less tectonically active transitional and post‐rift stages dominated by thermal subsidence gradually led to the healing of the rift‐related structural relief. Selective reactivation of rift faults testifies active tectonic inversion through compression from immediate post‐rift throughout evaporite deposition. These interpretations are put into the context of recent geochronological data of onshore dyke emplacement and the new age constraints for the end of deposition of the pre‐salt sequence. Therefore, we propose an earlier onset on rifting in the Campos Basin, at the Berriasian. Abstract : The rift system of in the North of Campos Basin records two distinct rift phases (RP1 and RP2). The RP1 and therefore the onset of rifting is interpreted to have occurred in the Berriasian.